Moderasi Beragama dari Toba bagi Indonesia: Potret Tantangan, Hambatan, dan Strategi Mewujudkannya - Agnes Novianti Permata Sari (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Religious moderation is essential for building a harmonious and tolerant society amid religious diversity. This study aims to assess the success of religious moderation programs in Toba district, which is home to various religious communities. The research focuses on the challenges hindering public understanding of religious moderation and explores ways to enhance awareness and implementation. Using a qualitative method, data were collected through interviews and direct observations. The findings indicate a need for broader understanding among Toba residents regarding the values of religious moderation. Socialization and training efforts should be directed toward local Ministry of Religious Affairs staff, religious instructors, and involve religious and traditional leaders to effectively disseminate the message of moderation. Support from the central Ministry of Religion—particularly in providing equitable budget allocations to regional offices—is also crucial for the successful implementation of the program. A structured and collaborative approach is necessary to ensure that the message of religious moderation reaches all levels of society and contributes to the maintenance of interreligious harmony.